Island 1:100,000 Kirkjubaejarklaustur Blatt nr. 78 (Kriegskarten- und Vermessungswesen, 1941)
1. Sonderausgabe VIII 1941 Relief shown by contours, form lines and spot heights. Sheets contain index to adjoining sheets and glossary. Color; 1:100,000